2017
DOI: 10.1177/0269881117699603
|View full text |Cite
|
Sign up to set email alerts
|

Effect of doxazosin on stress reactivity and the ability to resist smoking

Abstract: Preclinical findings support a role for α1-adrenergic antagonists in reducing nicotine motivated behaviors, but these findings have yet to be translated to humans. The current study evaluated whether doxazosin would attenuate stress-precipitated smoking in the human laboratory. Using a well-validated laboratory analogue of smoking-lapse behavior, this pilot study evaluated whether doxazosin (4 and 8 mg/day) versus placebo attenuated the effect of stress (vs. neutral imagery) on tobacco craving, the ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 38 publications
4
27
0
Order By: Relevance
“…This effect was most evident among participants receiving 4-mg/day doxazosin-those receiving 8 mg/day reported an increase in withdrawal symptoms during deprivation. As reported in the parent study and in prior investigations (Stoschitzky et al, 2003;Verplaetse et al, 2017), doxazosin increases heart rate, suggesting that the drug may paradoxically have sympathomimetic effects under certain circumstances. These effects may have strengthened at higher doses, potentially offsetting the beneficial effects of the drug on withdrawal symptoms.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This effect was most evident among participants receiving 4-mg/day doxazosin-those receiving 8 mg/day reported an increase in withdrawal symptoms during deprivation. As reported in the parent study and in prior investigations (Stoschitzky et al, 2003;Verplaetse et al, 2017), doxazosin increases heart rate, suggesting that the drug may paradoxically have sympathomimetic effects under certain circumstances. These effects may have strengthened at higher doses, potentially offsetting the beneficial effects of the drug on withdrawal symptoms.…”
Section: Discussionsupporting
confidence: 67%
“…Participants attended a premedication baseline assessment session and two laboratory testing sessions, including a nondeprivation session and a deprivation session. Adverse event and other methodological details not pertinent to the current report are described in the parent publication (Verplaetse et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Further prospective experimental studies manipulating EI abilities and stress reactivity are needed to confirm the causal inferences of our findings. In this regard, there are a set of human laboratory studies that have investigated smoking relapse behaviour through the manipulation of the stress response by medication and imagery inductions [49,50]. For example, Verplaetse et al [50] showed that a pharmacotherapeutic treatment aimed at attenuating the effect of stress by the use of doxazosin (α1-adrenergic antagonist) improved the ability to resist cravings and begin smoking.…”
Section: Plos Onementioning
confidence: 99%
“…In this regard, there are a set of human laboratory studies that have investigated smoking relapse behaviour through the manipulation of the stress response by medication and imagery inductions [49,50]. For example, Verplaetse et al [50] showed that a pharmacotherapeutic treatment aimed at attenuating the effect of stress by the use of doxazosin (α1-adrenergic antagonist) improved the ability to resist cravings and begin smoking. The evaluation or training of EI abilities in experimental studies could be a very informative step forward for understanding the mechanisms by which EI could influence smoking relapse.…”
Section: Plos Onementioning
confidence: 99%
“…With respect to NE α1 antagonists, three small phase II trials (N = 17-35) provided preliminary support for positive impacts on stress-relevant surrogate end points and short-term clinical outcomes for prazosin in AUD (Fox et al 2012a, Simpson et al 2009 and for doxazosin in tobacco smokers (Verplaetse et al 2017). However, a fourth small trial (N = 41) observed no effect of doxazosin on its primary clinical outcomes in patients with AUD (Kenna et al 2016).…”
Section: Stress-relevant Pharmacologic Treatmentsmentioning
confidence: 99%